2018
DOI: 10.1007/s00253-018-8832-9
|View full text |Cite
|
Sign up to set email alerts
|

Immediate response mechanisms of Gram-negative solvent-tolerant bacteria to cope with environmental stress: cis-trans isomerization of unsaturated fatty acids and outer membrane vesicle secretion

Abstract: Bacteria have evolved an array of adaptive mechanisms enabling them to survive and grow in the presence of different environmental stresses. These mechanisms include either modifications of the membrane or changes in the overall energy status, cell morphology, and cell surface properties. Long-term adaptations are dependent on transcriptional regulation, the induction of anabolic pathways, and cell growth. However, to survive sudden environmental changes, bacterial short-term responses are essential to keep th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 116 publications
(201 reference statements)
2
85
0
1
Order By: Relevance
“…The previously reported constitutive cti expression in solvent-treated bacteria led to the establishment of a Cti regulation model, according to which Cti activity is not controlled at the transcriptional level, but rather by simply allowing or prohibiting the active center of the enzyme to reach the double bond, which would depend only on membrane fluidity (Heipieper et al, 2010;Eberlein et al, 2018). The activation of cti expression in octanol-treated P. putida F1 cultures observed in our studies C. β-Galactosidase activity of pFCtiPP1 showing than Crp represses cti expression in P. putida F1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previously reported constitutive cti expression in solvent-treated bacteria led to the establishment of a Cti regulation model, according to which Cti activity is not controlled at the transcriptional level, but rather by simply allowing or prohibiting the active center of the enzyme to reach the double bond, which would depend only on membrane fluidity (Heipieper et al, 2010;Eberlein et al, 2018). The activation of cti expression in octanol-treated P. putida F1 cultures observed in our studies C. β-Galactosidase activity of pFCtiPP1 showing than Crp represses cti expression in P. putida F1.…”
Section: Discussionmentioning
confidence: 99%
“…Cti, which located in the cellular periplasm (Pedrotta and Witholt, 1999), is a cytochrome c-type protein, bearing a heme-binding motif essential for the cis to trans isomerization reaction (Holtwick et al, 1999). Moreover, the highest levels of the trans-UFA were found 30 min after the initiated stress, demonstrating cis-trans isomerization to be a fast adaptive response Eberlein et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fatty acid composition and pattern of TDA1 was the same as the one of strain P. putida KT2440 which was used as a control and benchmark. In addition, the gene for the cis-trans isomerase of unsaturated fatty acids (CTI), an important marker gene for the genus Pseudomonas (Palleroni, 2015;Eberlein et al, 2018), is present in the TDA1 genome (gene 13840) revealing more than 90% amino acid sequence identity with several Pseudomonas CTIs already present in the protein BLAST database (for example: Accession numbers Q8RJN7, A0A059V043, and F8FYU0). Also, the CTI phenotype, regularly given as solvent stress-depending increase in the trans/cis ratio of unsaturated fatty acids, was detected in the presence of 2,4-TDA in P. putida KT2440 (Figure 2).…”
Section: Carbon Source Growthmentioning
confidence: 99%
“…In microorganisms like bacteria, PLA 2 is activated under diverse stress conditions (Belosludtsev et al, 2014;Istivan and Coloe, 2006;Zheng et al, 2017). However, few studies have reported bacterial membrane changes under stress by heavy metals and aromatic compounds, and even fewer have described the changes in PL head groups or acyl chains under simultaneous Cr(VI) and phenol treatment (Eberlein et al, 2018;Markowicz et al, 2010;Pepi et al, 2008;Waranusantigul et al, 2011). The presence of these and other pollutants generates environmental signals whose perception is considered to occur at the cell membrane level (Sohlenkamp and Geiger, 2015).…”
Section: Introductionmentioning
confidence: 99%